PENGARUH MODAL INTELEKTUAL, STRUKTUR MODAL, DAN FAKTOR LAINNYA TERHADAP NILAI PERUSAHAAN - Wulan Aisyah Indirawati; Widyawati Lekok (E-Jurnal Akuntansi TSM, 2026)
The purpose of this research is to find empirical evidence related to the factors that influence the value of the company. This research will examine whether the variables of intellectual capital, managerial ownership, capital structure, audit committee, asset structure, and current ratio have an impact on the value of the company. Purposive sampling technique is the sampling method used in this study and uses the multiple regression method as a method for analyzing data. The data obtained comes from the financial statement of public manufacturing companies that are consistently listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. The sample used in this study was 80 companies with a total of 240 data that met the research criteria. The research results show that intellectual capital, capital structure, and the current ratio have an impact on company value, while other independent variables such as managerial ownership, audit committee, and asset structure do not affect company value. The research results show that intellectual capital, capital structure, and the current ratio have an impact on company value, while other independent variables such as managerial ownership, audit committee, and asset structure do not affect company value.